Divergent responses of primary production to increasing precipitation variability in global drylands. (26th July 2021) - Hou, Enqing; Litvak, Marcy E.; Rudgers, Jennifer A.; Jiang, Lifen; Collins, Scott L.; Pockman, William T.; Hui, Dafeng; Niu, Shuli; Luo, Yiqi
Abstract: Interannual variability in precipitation has increased globally as climate warming intensifies. The increased variability impacts both terrestrial plant production and carbon (C) sequestration. However, mechanisms driving these changes are largely unknown. Here, we examined mechanisms underlying the response of aboveground net primary production (ANPP) to interannual precipitation variability in global drylands with mean annual precipitation (MAP) <500 mm year −1, using a combined approach of data synthesis and process‐based modeling. We found a hump‐shaped response of ANPP to precipitation variability along the MAP gradient. The response was positive when MAP < ~300 mm year −1 and negative when MAP was higher than this threshold, with a positive peak at 140 mm year −1 . Transpiration and subsoil water content mirrored the response of ANPP to precipitation variability; evaporation responded negatively and water loss through runoff and drainage responded positively to precipitation variability. Mean annual temperature, soil type, and plant physiological traits all altered the magnitude but not the pattern of the response of ANPP to precipitation variability along the MAP gradient. By extrapolating to global drylands (<500 mm year −1  MAP), we estimated that ANPP would increase by 15.2 ± 6.0 Tg C year −1 in arid and hyper‐arid lands and decrease by 2.1 ± 0.5 Tg C year −1 in dry sub‐humid lands under future changes in interannual precipitation variability. Thus, increases in precipitation variability will enhance primary production in many drylands in the future. Abstract : Both observational data and modeling analyses showed that the effect of interannual precipitation variability on aboveground net primary production was positive when mean annual precipitation <~300 mm year −1 and negative when mean annual precipitation was higher than this threshold. Modeling analyses also showed that the positive effect peaked at 140 mm year −1 . Transpiration and subsoil water content mirrored the response of aboveground net primary production to precipitation variability; evaporation responded negatively and water loss through runoff and drainage responded positively to precipitation variability.